2020
DOI: 10.1016/j.fsi.2020.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional insights into a novel teleost malectin from big-belly seahorse Hippocampus abdominalis

Abstract: Malectin is a carbohydrate-binding lectin protein found in the endoplasmic reticulum (ER). It selectivity binds to Glc 2 -N-glycan and is involved in a glycoprotein quality control mechanism. Even though malectin may play a role in immunity, its role in innate immunity is not fully known. In the present study, we identified and characterized the malectin gene from Hippocampus abdominalis (HaMLEC). We analyzed sequence features, spatial expression levels, temporal expression profiles upon immune responses, bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Malectin binds to Glc2-N-glycans, whereas calnexin/calreticulin binds to Glc1-N-glycans [6,23,24]. Malectins in the invertebrate scallop Chlamys farreri and big-belly seahorse Hippocampus abdominalis are regulated by pathogen infection [25,26], suggesting their participation in immunity. Orthologs of malectins have been identified in D. melanogaster and A. aegypti, but have not been studied yet [27,28].…”
Section: Insect Lectinsmentioning
confidence: 99%
“…Malectin binds to Glc2-N-glycans, whereas calnexin/calreticulin binds to Glc1-N-glycans [6,23,24]. Malectins in the invertebrate scallop Chlamys farreri and big-belly seahorse Hippocampus abdominalis are regulated by pathogen infection [25,26], suggesting their participation in immunity. Orthologs of malectins have been identified in D. melanogaster and A. aegypti, but have not been studied yet [27,28].…”
Section: Insect Lectinsmentioning
confidence: 99%
“…It is known as ‘South ginseng’ in traditional Chinese medicine (TCM) culture. Pharmacological studies have shown that Hippocampus have anti-oxidation ( Chen et al, 2010 , Kim et al, 2019 , Zheng et al, 2012 ), anti-inflammation ( Chen et al, 2015 , Tharuka et al, 2019 , Wu et al, 2020 ), anti-depressant ( Li et al, 2020 ), anti-hypertension ( Je et al, 2020 ), anti-prostatic hyperplasia ( Xu et al, 2014 ), anti-virus ( Sandamalika et al, 2021 , Tharuka et al, 2019 , Udayantha et al, 2021 ), anti-apoptotic ( Kodagoda et al, 2022 , Sellaththurai et al, 2020 , Wijerathna et al, 2022 ), anti-fatigue ( Guo et al, 2017 , Zhang et al, 2019 ), and other functions ( Pangestuti et al, 2013 , Sellaththurai et al, 2020 , Yuan et al, 2018 ). And those pharmacological action are mainly related to their active ingredients, including amino acids ( Ge et al, 2019 , Sari et al, 2017 , Zhao, 2018 ), abundant proteins (peptides and oligopeptides) ( Je et al, 2020 , Pangestuti et al, 2013 ), fatty acids ( Huang & Xu, 2016 , Shen et al, 2016 , Su & Xu, 2015 ), nucleosides ( Wei et al, 2015 , Zhao et al, 2011 ), steroids ( Wu et al, 2017 , Zhao, 2018 ), and other small molecular compounds ( Si et al, 2018 , Zhao, 2018 ).…”
Section: Introductionmentioning
confidence: 99%